2018
DOI: 10.1021/acs.jpcc.8b06226
|View full text |Cite
|
Sign up to set email alerts
|

Electron Beam-Induced Surface Activation of Metal–Organic Framework HKUST-1: Unraveling the Underlying Chemistry

Abstract: The local chemical activation of surfaceanchored metal−organic frameworks is a novel electron beam-based lithographic technique with a high potential for the fabrication of chemically and spatially well-defined nanostructures in the sub-10 nm regime. In this context, we have performed a detailed investigation of electron beaminduced surface activation (EBISA) on the surface-anchored layers of HKUST-1 and copper(II) oxalate with the subsequent autocatalytic growth (AG) of deposits from the precursors Fe(CO) 5 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 72 publications
4
29
0
Order By: Relevance
“…This observation is confirmed by the fact that measured interplanar distances (<dhkl> = 0.207 ± 0.004 nm) are in excellent agreement with the (111) interplanar distance of Cu (d111 = 0.2087 nm). Based on the previous results on the effect of e-beam on the chemi cal bounding of MOFs [15][16][17][18] and similar reason for growth of Pt and Au NPs from organometallic precursors [30,31], the possibility of the growth of the NPs from the constituent parts of HKUST-1 is due to breaking of bonds between copper and organic part. Moreover, the growth of pure Cu NPs instead of its oxide form is explained by a lower oxidation potential of Cu and relatively weak Cu COO bond energy, which promote the metallic state [15].…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…This observation is confirmed by the fact that measured interplanar distances (<dhkl> = 0.207 ± 0.004 nm) are in excellent agreement with the (111) interplanar distance of Cu (d111 = 0.2087 nm). Based on the previous results on the effect of e-beam on the chemi cal bounding of MOFs [15][16][17][18] and similar reason for growth of Pt and Au NPs from organometallic precursors [30,31], the possibility of the growth of the NPs from the constituent parts of HKUST-1 is due to breaking of bonds between copper and organic part. Moreover, the growth of pure Cu NPs instead of its oxide form is explained by a lower oxidation potential of Cu and relatively weak Cu COO bond energy, which promote the metallic state [15].…”
Section: Resultsmentioning
confidence: 81%
“…HKUST-1 is also a representative class of MOFs that are easy to grow on different surfaces following a layer-by-layer approach [26], which makes it promising for applied research. Moreover, the compound has been recently investigated to reveal the mechanism of electron-induced decomposition and the reason for NPs formation [15][16][17][18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, for EBISA a suitable combination of substrate and precursor is a prerequisite, that is, the substrate must be chemically altered by the electron beam and the precursor molecule must be susceptible to the altered site. Substrates that are known to fulfill the prerequisite are silicon oxide [ 10 , 12 ], rutile TiO 2 (110) [ 13 ], thin layers of porphyrin molecules [ 14 15 ], and surface-anchored metal-organic frameworks (SURMOFs) [ 16 17 ]. For oxide surfaces it is known that the activation mechanism is based on reactive oxygen vacancies, which are locally created by electron-stimulated oxygen desorption [ 18 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have demonstrated that focused electron beam induced processing (FEBIP) has high potential for the controlled bottom-up fabrication of metallic 3D nanostructures [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Furthermore, the basic processes during FEBIP are understood to more and more detail leading to developments towards more diverse, cleaner and more defined deposits for various potential applications [7,[15][16][17][18]. The method employs a focused electron beam to induce local dissociation of surface-absorbed metal organic precursor molecules supplied from the gas-phase.…”
Section: Introductionmentioning
confidence: 99%